Effects of partial replacement of dietary flour meal with seaweed polysaccharides on the resistance to ammonia stress in the intestine of hybrid snakehead (Channa maculatus ♀ × Channa argus ♂). Issue 127 (August 2022) - Zuo, Zhiheng; Wang, Shaodan; Wang, Qiujie; Wang, Dongjie; Wu, Qiuping; Xie, Shaolin; Zou, Jixing
Abstract: The purpose of this study was to evaluate the effects of partial replacement of dietary flour meal with seaweed polysaccharides on survival rate, histology, intestinal oxidative stress levels, and expression of immune-related genes in hybrid snakeheads under acute ammonia stress. Four experimental diets were set: (C) basal diet with 0% of seaweed polysaccharides as the control group, (MR) basal diet with 10% of seaweed polysaccharides, (HR) basal diet with 15% of seaweed polysaccharides, (HF) basal diet with 10% of fish oil. After 60 days of feeding, fish fed with the diet of C group were sampled as the control group, and other fish were exposed to ammonia nitrogen for 48 h. Two concentrations of total ammonia nitrogen (TAN) were used in this study: 120 mg/L TAN (low concentration exposure group), and 1200 mg/L TAN (high concentration exposure group). After exposure to ammonia nitrogen for 48 h, fish were sampled. The results indicated that adding seaweed polysaccharides to the diet could improve the survival rate of hybrid snakeheads under high concentration of ammonia stress. Histopathological analysis demonstrated multiple abnormalities in gills and intestines after exposure to two concentrations of TAN. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and lactate dehydrogenase (LDH) were all increased in the MR group under two concentrations of TAN stress. The mRNA abundance of immune-related genes in fish intestinal tissues was significantly induced or inhibited. These results suggested that partial replacement of dietary flour meal with seaweed polysaccharides improved the ability of hybrid snakeheads to resist ammonia stress. Graphical abstract: Image 1 Highlights: Adding seaweed polysaccharides to the diet can improve the survival rate of hybrid snakeheads under ammonia stress. Under ammonia stress, 10% seaweed polysaccharides had the most significant protective on the intestines of hybrid snakeheads. The low content of flour in the feed will weaken the intestinal resistance of hybrid snakehead to ammonia nitrogen.